2001
DOI: 10.1111/j.1469-7793.2001.0869e.x
|View full text |Cite
|
Sign up to set email alerts
|

Foot sole and ankle muscle inputs contribute jointly to human erect posture regulation

Abstract: International audience1. In order to assess the relative contribution and the interactions of the plantar cutaneous and muscle proprioceptive feedback in controlling human erect posture, single or combined vibratory stimuli were applied to the forefoot areas and to the tendons of the tibialis anterior muscles of nine standing subjects using various vibration frequency patterns (ranging from 20 to 80 Hz). 2. The variations in the centre of foot pressure, ankle angle and the EMG activities of the soleus and tibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
226
1
14

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(255 citation statements)
references
References 37 publications
14
226
1
14
Order By: Relevance
“…Another finding was that the complaint foam support surface increased the movements of the lower body segments, e.g., the knee and hip movements proportionally more than shoulder and head movements, see table 2. These observations are in line with several previous reports showing that changed sensory information from vision and proprioception can have a major effect on postural control and the multi-segmented body movements (Kavounoudias et al 1999;Perry et al 2000;Kavounoudias et al 2001;Blackburn et al 2003;Vuillerme et al 2005).…”
Section: Effect Of Foam Support Surface On Body Movements and Torque supporting
confidence: 92%
“…Another finding was that the complaint foam support surface increased the movements of the lower body segments, e.g., the knee and hip movements proportionally more than shoulder and head movements, see table 2. These observations are in line with several previous reports showing that changed sensory information from vision and proprioception can have a major effect on postural control and the multi-segmented body movements (Kavounoudias et al 1999;Perry et al 2000;Kavounoudias et al 2001;Blackburn et al 2003;Vuillerme et al 2005).…”
Section: Effect Of Foam Support Surface On Body Movements and Torque supporting
confidence: 92%
“…For example, Kavounoudias et al 31 reported that vibration (high frequency and low amplitude) of skin mechanoreceptors of anterior and/or posterior areas of one or both soles yield spatially oriented whole-body tilts for which the direction depends on the foot areas stimulated. As suggested by these authors, this is a compelling evidence that cutaneous afferent messages from the main supporting zones of the feet have spatial relevance to inform the central nervous system (CNS) about the body position with respect to the vertical reference.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Dietz et al (1992) and Duysens et al (2000) have argued that GTOs signal load in humans as well. In addition, cutaneous afferents from plantar mechanoreceptors in the foot have been shown to be important for postural control (Kavounoudias et al 2001) and compensatory postural reflexes elicited in response to a forward fall while standing (Do et al, 1990).…”
Section: Modulation Of Ankle Muscle Postural Reflex Magnitude Followimentioning
confidence: 99%
“…It is believed that Ib afferents from golgi tendon organs (GTOs) provide load information to the spinal cord (Dietz et al, 1992;Duysens et al, 2000). In addition to Ib afferents from GTOs, cutaneous mechanoreceptors in the sole of the foot are in an optimal location to sense limb load and have been recently shown to be important in standing balance (Kavounoudias et al, 2001). …”
Section: Introductionmentioning
confidence: 99%